Analysis of environmental health determinants of drinking water quality in urban slums - Arliatin, Arliatin; Hilal, Achmad; Susanti, Susi; Andrianys, Irma; Syahrir, Muhammad (Journal of Midwifery and Nursing, 2025)
Urban slums often face serious drinking water quality challenges due to poor sanitation facilities and waste management, which contribute to high public health risks. This study aimed to analyze the environmental health determinants, including access to clean water, sanitation facilities and waste management practices, on drinking water quality based on physical, chemical and microbiological indicators. The study used a quantitative research design with a correlational approach, involving five urban slums as the study population. Data were collected through field observation and water quality testing, then analyzed using Pearson correlation test and multiple linear regression. The results showed that access to clean water had a significant negative relationship with microbial contamination levels (r = -0.899, p < 0.05). In addition, sanitation facilities and waste management practices significantly influenced drinking water quality, with areas with better facilities showing better water quality. However, discrepancies in microbiological indicators were found across areas, indicating the need for integrated interventions. This study confirms the importance of improved sanitation infrastructure, community education and water management in addressing water quality challenges in slums. The implications of this study can serve as a foundation for more effective policy making in environmental and public health management.